A discussion of Alexander S. Kirschner's A Theory of Militant Democracy: The Ethics of Combatting Political Extremism. Issue 3 (7th September 2015) - Mudde, Cas
Abstract : The legitimacy claims of liberal democratic states are typically couched in the language of individual rights and the rule of law. But contemporary liberal democratic states increasingly appeal to a logic of security, law and order, and the need to combat "political extremism." This logic plays out in Ukraine, Egypt, and Turkey, and in Greece and Germany, but also in the U.S., France, and the UK. It is an increasingly important feature of politics in societies that may be experiencing a rough "transition to democracy, " but also in societies that are conventionally regarded as "consolidated democracies." The normative and practical challenges presented by this situation are fundamental. Alexander S. Kirschner's A Theory of Militant Democracy: The Ethics of Combatting Political Extremism offers one interesting take on these issues, which cut to the core of political science as a discipline. We have thus invited a range of political scientists from a variety of subfield and methodological perspectives to comment on the book and on the broader topic the book engages—the ethics of combatting political extremism and indeed the very political construction of "political extremism." — Jeffrey C. Isaac